Handbook of hazardous chemical properties - Cheremisinoff, Nicholas P. (Butterworth-Heinemann, 2000)
This book provides information on nearly 700 chemicals of commercial and industrial importance, as well as health (toxicological) and safety handling information. It provides chemical specific information pertinent to safe handling and transportation of chemicals, worker protection, emergency response information to address spills, explosions on fire situations, and chemical stability/reactivity data. It is designed as a standard reference handbook for chemical engineers, safety engineers, toxicologists, fire safety specialists, chemists, laboratory and plant technicians.